2017
DOI: 10.1080/19476337.2017.1317667
|View full text |Cite
|
Sign up to set email alerts
|

The bioactive compounds, antioxidant capacity, and color intensity in must and wines derived from grapes processed by pulsed electric field

Abstract: The aim of this work was to study the effect of pulsed electric field (PEF) treatment on the content of bioactive compounds (total phenols, total flavonoids, monomeric anthocyanin content), antioxidant capacity, color intensity (CI), and sensory quality of wines derived from three varieties of grapes (Muscat Ottonel, Pinot Noir, and Merlot). PEF treatment resulted in an increase in all bioactive compounds, and consequently, an increase in their antioxidant capacity, which was evaluated by different methods. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It was found that melatonin is present in a lot of different types of foods and food supplements. The quantity of melatonin in the most common foods is variable: banana -0.47 ng/g [7], apple -0.05 ng/g [8], kiwifruit 0.02 ng/g [8], pineapple -0.04 ng/g [8], strawberry -0.01 ng/g [8], montmorency tart cherry -13.46 ng/g [9], orange -0.15 ng/g [10], mango -0.70 ng/g [10], papaya -0.24 ng/g [10], tomato -8-16 pg/g [11,12], red wine -17.07 ng/g [13,14], beer -1.43 ng/g [13], bread crumb 3 -1.57 ng/g [15], walnuts -1.0 ng/g [15,16] , olive oil -53-119 pg/mL [17], almonds -39 ng/g [18], coffea canephora -115.25 ± 6µg/ g [19], beef -2.1 ng/g [20], salmon -3.7 ng/g [20].…”
mentioning
confidence: 99%
“…It was found that melatonin is present in a lot of different types of foods and food supplements. The quantity of melatonin in the most common foods is variable: banana -0.47 ng/g [7], apple -0.05 ng/g [8], kiwifruit 0.02 ng/g [8], pineapple -0.04 ng/g [8], strawberry -0.01 ng/g [8], montmorency tart cherry -13.46 ng/g [9], orange -0.15 ng/g [10], mango -0.70 ng/g [10], papaya -0.24 ng/g [10], tomato -8-16 pg/g [11,12], red wine -17.07 ng/g [13,14], beer -1.43 ng/g [13], bread crumb 3 -1.57 ng/g [15], walnuts -1.0 ng/g [15,16] , olive oil -53-119 pg/mL [17], almonds -39 ng/g [18], coffea canephora -115.25 ± 6µg/ g [19], beef -2.1 ng/g [20], salmon -3.7 ng/g [20].…”
mentioning
confidence: 99%
“…Similar results were observed in Rios-Corripio et al, (2022) [ 45 ], wherein the sample treated with PEF (18.8 kV/cm) on a pomegranate-fermented beverage showed constant total phenol and flavonoid content during 56-day storage compared to other pasteurization technologies. Exposure to intense voltage could increase the antioxidant capacity due to the release of phenolic compounds; the treatment of PEF (7 kV/cm) on wines increases the bioactive compounds [ 49 ]. Furthermore, treatment of PEF effectively reduces the total aerobic bacteria without altering antioxidant compounds such as anthocyanin and the total phenolic contents in pomegranate juice [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, mannoprotein enrichment of certain types of wine occurs during yeast autolysis in the "aging-on-the-lees step." Not only is this a slow process, but it can negatively impact wine quality, increasing the Vicaş et al (2017) accelerating the release of β-glucanase and protease, leading to the degradation of the cell wall and, subsequently, the rapid release of intracellular components, such as polysaccharides and glutathione (Martinez et al, 2016). In the aging-on-the-lees group containing untreated yeast, no mannoproteins were detected in the first 7 days.…”
Section: Accelerating the Release Of Mannoproteins From Saccharomyces...mentioning
confidence: 99%